Conclusion : où allons-nous en études stratégiques? Les dix commandements du « nouveau stratège » - David, Charles-Philippe (Études internationales, 1989)
If Strategic Studies are to progress and remain relevant as a fîeld of social sciences and a sub-field of international relations, they have to be more pluralistic, interdisciplinary and innovative. If there is no work at these three levels, strategic thought may become more and more marginalized This short paper defines ten ways by which the "new strategist" may reform and help the cause of strategic Studies.